Drop motion during mass transfer accompanied by interphase convection - Anatolii G. Titov; Zalina R. Rusinova; Ekaterina A. Kalimullina; Anatoliy M. Vorobev (Chimica Techno Acta, 2022)
The article deals with the experimental study of the mass transfer of acetic acid from the dispersed phase (butyl acetate) to the continuous phase (water). The experiments were carried out on a laboratory column with single floating drops. The presence of the Marangoni effect during the movement of drops and its influence on the trajectories of movement of drops and the kinetics of mass transfer during extraction are shown. The influence of the Marangoni effect is most clearly observed when the driving force of the process is 0.1...0.2 mol/l.